Undergraduate students’ perception toward Edmodo integration into EFL classroom: An interview study - Zhintya Dewi Intan Permata Sari; Moh. Arif Mahbub (Journal of Research on English and Language Learning (J-REaLL), 2023)
This qualitative interview study (Kvale, 2007) aims to explore students’ perceptions about the integration of Edmodo into an Indonesian EFL writing classroom. Three participants enrolled in the Advanced Paragraph Writing course at one of the private universities in the East Java Province, Indonesia, voluntarily involved in the current study. Drawing upon semi-structured interviews,  the thematic analysis (Braun & Clarke, 2006) showcased that the participants felt so comfortable with Edmodo as a learning management system (LMS) integrated into their classroom. Not surprisingly, they recommended this app to be incorporated into their classroom in the future as a complement to the traditional face-to-face classroom. Finally, we drew conclusions, limitations, practical implications, and recommendations.